Patient Safety in the Commonwealth of Massachusetts Current Status and Opportunities for Improvement - Schneider, Eric C. (RAND Corporation, 2014)
In a RAND study about the landscape of patient safety in Massachusetts, researchers interviewed expert observers (patients, health care leaders, academic experts, advocates, and others) about progress to date and future opportunities to produce safer patient care. This report summarizes the results of the interviews and suggests several questions that could guide the design of an organized effort to improve patient safety in Massachusetts.